2012
DOI: 10.1002/jor.22262
|View full text |Cite
|
Sign up to set email alerts
|

Statins may reduce femoral osteolysis in patients with total Hip arthroplasty

Abstract: ABSTRACT:In experimental studies, statin use has been associated with reduction of osteoclastic activity and promotion of bone formation around implants. Moreover, a large clinical study recently reported a substantially reduced risk of revision for aseptic loosening among statin users with THA. Our objective was to evaluate the influence of statin use on the development of femoral osteolysis within 5 years after THA. We conducted a case-cohort study including all THAs presenting with femoral osteolysis at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…Obesity has been deemed a relative contraindication for hip replacement and a risk factor for complications and prosthesis failure . Although obesity was shown to increase the risk of early revision due to aseptic loosening and/or osteolysis by almost fivefold, statins were suggested to reduce femoral osteolysis in hip arthroplasty . However, some studies revealed obesity paradox, in which obesity or its correlates provided some protective effect in hip replacement .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity has been deemed a relative contraindication for hip replacement and a risk factor for complications and prosthesis failure . Although obesity was shown to increase the risk of early revision due to aseptic loosening and/or osteolysis by almost fivefold, statins were suggested to reduce femoral osteolysis in hip arthroplasty . However, some studies revealed obesity paradox, in which obesity or its correlates provided some protective effect in hip replacement .…”
Section: Discussionmentioning
confidence: 99%
“…34 Although obesity was shown to increase the risk of early revision due to aseptic loosening and/or osteolysis by almost fivefold, 35 statins were suggested to reduce femoral osteolysis in hip arthroplasty. 36 However, some studies revealed obesity paradox, in which obesity or its correlates provided some protective effect in hip replacement. 37 Further, the risk of femoral osteolysis in some normal-weight patients was higher compared with overweight patients.…”
Section: In Silico Research On Periprosthetic Osteolysismentioning
confidence: 99%
“…The relative risk ratio after adjustment for confounders (age, sex, activity level, BMI, diagnosis, bearing surface, type of stem) was 0.38 (95% CI 0.15; 0.99). This analysis did not have sufficient follow-up length to determine whether the risk of revision was lower in the statin ever-use group 49 .…”
Section: There Is An Established Research Base For a Class Of Drug Knmentioning
confidence: 99%
“…The discordance between observational studies and randomized trials is explained by selection bias, confounding by indication, or a “healthy user” phenomenon 117 . Systemically administered statins are associated with a reduced risk of aseptic revision and osteolysis in at least two THA studies 118,119 . Yet, evidence from local delivery of statins on orthopedic implants is so far inconclusive.…”
Section: Medicationsmentioning
confidence: 99%